2011
DOI: 10.1002/jmri.22824
|View full text |Cite
|
Sign up to set email alerts
|

Impact of partial volume effects on visceral adipose tissue quantification using MRI

Abstract: Purpose: To quantitatively estimate the impact of partial volume effects on visceral adipose tissue (VAT) quantification using typical resolution magnetic resonance imaging (MRI). Materials and Methods:Nine normal or overweight subjects were scanned at central abdomen levels with a water-saturated, balanced steady-state free precession (b-SSFP) sequence. The water-saturation effectiveness was evaluated with region-of-interest analysis on fat, muscle, bowel, and noise areas. The number of full-volume (FV) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The infiltration of macrophages and CD-8-positive T cells in the EAT of patients subjected to bypass was greater than patients who underwent surgery for aortic or mitral valve replacement [8]. Finally, patients with advanced CHD exhibited lower epicardial adiponectin levels, which may contribute to the increased cardiovascular risk [9-11]. …”
Section: Introductionmentioning
confidence: 99%
“…The infiltration of macrophages and CD-8-positive T cells in the EAT of patients subjected to bypass was greater than patients who underwent surgery for aortic or mitral valve replacement [8]. Finally, patients with advanced CHD exhibited lower epicardial adiponectin levels, which may contribute to the increased cardiovascular risk [9-11]. …”
Section: Introductionmentioning
confidence: 99%
“…Although sensitive to coil profile effects, T 1 ‐weighted imaging is a simple and reliable technique for investigating large fat depots (7, 8). However, it needs to be combined with effective segmentation approaches to separate adipose tissue from nonadipose tissue, especially in the presence of strong partial volume effects while investigating small fat depots like the VAT and IMAT compartments (10, 11). More recently T 1 ‐weighted imaging has been combined with water suppression (12, 13) and with dual acquisitions using water suppression and fat suppression (14) for the development of clustering image‐processing approaches to automatically segment the adipose tissue into different compartments.…”
mentioning
confidence: 99%
“…The impact of partial volume effect is particularly important for MRI, as the voxel size is generally much larger than that of CT. Studies have shown that ignoring this effect in MRI by establishing binary voxel-based segmentations introduces significant errors in quantitative measurements. 38,39 Most of these errors are associated with accurate quantification of small volumes, such as lesions, where the boundary contributes significantly in the total volume estimation. In the current breast density study, however, the quantification was carried out by averaging a large number of voxels, where the partial volume effects may be largely alleviated.…”
Section: Discussionmentioning
confidence: 99%